Dendritic Cell Migration Toward CCL21 Gradient Requires Functional Cx43 - Ruez, Richard; Dubrot, Juan; Zoso, Alice; Bacchetta, Marc; Molica, Filippo; Hugues, Stéphanie; Kwak, Brenda R.; Chanson, Marc (Frontiers in Physiology, 2018)
Dendritic cells (DCs) travel through lymphatic vessels to transport antigens and present them to T cells in lymph nodes. DCs move directionally towards lymphatics by virtue of their CCR7 and a CCL21 chemotactic gradient. We evaluated in vivo and in bone marrow-derived dendritic cells (BMDCs) whether the gap junction protein Cx43 contributes to CCL21/CCR7-dependent DC migration in wild-type (WT) mice, heterozygous (Cx43+/-) mice and mice expressing a truncated form of Cx43 lacking its regulatory C-terminus (Cx43K258/-). In a model of flank skin inflammation, we found that the recruitment of myeloid DCs (mDCs) to skin draining lymph nodes was reduced in Cx43K258/- mice as compared to WT and Cx43+/- mice. In addition, the migration of Cx43K258/- BMDCs towards CCL21 was abolished in an in vitro chemotactic assay while it was only reduced in Cx43+/- cells. Both mutant genotypes showed defects in the directionality of BMDC migration as compared to WT BMDCs. No difference was found between the three populations of BMDCs in terms of expression of surface markers (CD11c, CD86, CD80, CD40, MHC-II, CCR7) after differentiation and TLR activation. Finally, examination of the CCR7-induced signaling pathways in BMDCs revealed normal receptor-induced mobilization of intracellular Ca2+. These results demonstrate that full expression of an intact Cx43 is critical to the directionality and rate of DC migration, which may be amenable to regulation of the immune response.